Optimizing irbesartan spherical agglomerates through principal component analysis and experimental design - Gorde, V. D.; Rachh, Punit R.; Mankar, S. D.; Amin, Saurin (Creative Pharma Assent, 2024)
Background: This study explores the amalgamation of crystallization and agglomeration through spherical crystallization, aiming to develop the spherical crystals of Irbesartan with improved micromeritic properties. The main objective is to use spherical crystallization techniques to improve the micromeritic characteristics of Irbesartan, which has poor flow and compressibility because of its crystal habit. Methodology: A solvent change approach was utilized to synthesize spherical agglomerates of Irbesartan. Several system parameters, including the amount of bridging liquid, the rate of stirring, and the concentration of the polymer, were tuned to enhance the particle size distribution and mechanical qualities. SEM, GC, PXRD, DSC, and FTIR analyses characterised the spherical crystals. Result and Discussion: The study demonstrated that spherical crystallization significantly enhanced Irbesartan's micromeritic properties. The angle of repose of optimized agglomerates was reduced by around 52%, indicating improved considerably flowability of irbesartan. The sphericity of the crystals was validated by SEM examination (shape factor: 0.996), and the solvent levels were found to be within allowable bounds by GC analysis. PXRD data showed no polymorphism alterations, and DSC/FTIR analyses confirmed that the excipients and drug were compatible. Conclusion: This process provides a feasible alternative to classic granulation and agglomeration procedures, resulting in better flow, compressibility, and spherical crystals. It streamlines the Irbesartan formulation, improving efficiency and uniformity, reducing manufacturing costs, higher tablet consistency, and enhancing patient compliance.